Implementation Of Deep Learning Strategies To Improve The Reading Ability Of Kepong Elementary School Students In Malaysia - Ahmad Mughni; Ismail Saleh Nasution (Lembaga Riset dan Inovasi Almatani, 2026)
This research is based on observations indicating that learning activities in Indonesian language lessons, particularly those aimed at increasing students’ reading interest and speaking skills at Sanggar Bimbingan Muhammadiyah Kepong, have not been effective. Several factors contribute to this issue: (1) teachers do not use appropriate instructional media to enhance speaking skills due to limited time to prepare learning materials, and (2) students’ learning outcomes related to speaking skills, especially in the topic of healthy and unhealthy environments, remain low. This research and development study aims to examine the effectiveness of a Pop-Up Book–based serial picture media in improving the speaking skills of second-grade elementary students. The research used a pre-experimental method with a One-Group Pretest–Posttest design involving four second-grade students at SD Sanggar Bimbingan Kepong, Malaysia. Data were collected through a multiple-choice test consisting of ten items administered during the pretest and posttest stages. The results indicate an increase in the posttest score (81.67) compared to the pretest score (38.33). The normality test shows that the data are normally distributed (pretest sig. = 0.528; posttest sig. = 0.391). The paired sample t-test reveals a significance value of 0.000 < 0.05, indicating that the Pop-Up Book 3D media is effective in improving students’ speaking skills and reading interest, as well as making the learning process more active, enjoyable, and meaningfu